Dinamica di lungo periodo del sistema industriale italiano. Un'indagine empirica (1911-1991) - Giulio Cianelli; Riccardo Leoncini; Anna Montini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2000)
– The investigation of long-tern economic growth and structural change in an economic systems constitutes an issue with a long tradition in economics. The aim of this paper is to analyse, from an econometric point of view, the Italian manufacturing system during the XX century. In particular, using a quite large dataset based on Industrial Census, we deal with the following aspects: (i) the role of structural changes, (ii) the role of convergence and/or persistence of growth rates, and finally, (iii) the impact of measures of specialization and of variety on economic growth. The main findings seem to support an idiosyncratic view of the Italian industrial development with respect to the well-established literature on the topic. In particular, two points emerge: the stability of the model of production specialization along the period considered, and the role of variety of industrial environment as one of the leading factors in spurring coal industrial growth
Keywords: 330